Pengembangan E-Modul Pembelajaran Biologi Berbasis 3D Pageflip pada Materi Klasifikasi Makhluk Hidup untuk Siswa Kelas VII SMP: Development of E-Learning Module 3D Biology Based on Material Classification Pageflip Beings for Seventh Grade Students of SMP - Muhammad Khidayatullah Irfan; Upik Yelianti; Muhaimin Muhaimin (Universitas Jambi, 2019)
Education is now entering an era that encourages the use of technology to support the learning process. One such technology is the 3D Pageflip media which combines interactive simulations with text, images, videos and animations. This study aims is to develop the product of 3D Pageflip based e-module about classification of living things, as well as to determine student’s perceptions of the e-modules. This development research uses the ADDIE’s model. The e-module of 3D Pageflip are validated by media expert and content expert. The results of the validation of material experts obtained a score about 87% which was categorized as